Learning styles of biological sciences students at the university - Sánchez Horna, José Miguel (2019)
The purpose of the research was to determine the learning style of biological science students considering the possible effects of the variables, sex, political ideology and school of origin, on a sample of 59 students consisting of 40 entering and 19 next to graduate of the career of Biological Sciences of the Ricardo Palma University. The study had a quantitative, substantive, non-experimental design, and descriptive cross-section. The data was collected from the Kolb version E learning style instrument, the result indicates that the learning style present in the students who start the career is the usher with 55%, while the predominant style of the students who conclude is the assimilator with 57.89% Concrete learning styles are predominant in the students of the first cycle to be present in 65% of these, however the abstract learning styles are majority in the students of the tenth cycle reach 89.47%. The style of accommodating learning is higher in males (72.2%) than in females (40.9%) of the first cycle, however in the students of the tenth cycle, the assimilative style is higher in women (66.7%) than in men (50%).